Pengaruh Penggunaan Sistem Informasi Manajemen Berbasis Digital Terhadap Efisiensi Administrasi Pendidikan - Sari, Rika Yohana; Subandi, Ahmad; Irsyad, Irsyad (Academy of Social Science and Global Citizenship Journal, 2024)
This research aims to explore the concepts, characteristics and impact of using digital-based Management Information Systems (SIM) on the efficiency of educational administration. The method applied is library research or literature study, where researchers collect information from sources such as books and documents that are relevant to the research focus. The information collected is then analyzed qualitatively. Research findings show that the use of digital-based information systems has a significant influence on the efficiency of educational administration. This system enables the integration of information technology, automation of administrative tasks, and integrated management of data from various sources, which ultimately supports better decision making. SIM also comes with strong security policies and sensitive data protection mechanisms. The use of digital SIMs provides benefits such as increased data accessibility, reduced human error, and increased data accuracy. Educational institutions can manage resources more efficiently, improve communication and collaboration, and track performance in a more timely manner. Factors that influence the use of digital SIMs include technological infrastructure readiness, human resource capabilities, management support, and security policies.